Multicomponent reactions involving phosphines, arynes and aldehydes - Bhunia, Anup; Kaicharla, Trinadh; Porwal, Digvijay; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2014)
Although nucleophilic phosphine-catalysis is a powerful tool for the construction of various carbocycles and heterocycles, the reactions in which phosphines are incorporated into the final product are rare, and the reports on phosphine addition to highly electrophilic arynes are scarce. Herein, we report the phosphine triggered multicomponent reaction of arynes and aldehydes, which takes place via the formal [3+2] cycloaddition of an initially generated 1,3-phosphonium zwitterion from phosphines and arynes with aldehydes. The reaction resulted in the formation of a diverse range of stable pentacovalent phosphoranes in good yields based on the benzooxaphosphole system.